Self-Regulated Learning and Mathematical Anxiety in Relation to Critical Thinking Ability - Fitri Yani; Asih Miatun (Lectura: Jurnal Pendidikan)
Mathematics has a significant positive impact on the advancement of science and technology, as well as the development of information and communication technologies.